(untitled) (Journal of Global Accounting, 2025)
The general objective of this study was to assess the effect of bank charges on customers’ bank switching behaviour in Nigerian banking industry. The study is descriptive in nature and data were collected through structured questionnaire and face to face interview. 200 questionnaires were administered to the respondents but only 185 questionnaires were completed and returned to the researcher for data analysis. However, the populations of the study were drawn from five deposit money banks in Damaturu randomly which they are; First Bank Plc, GT Bank Plc, Keystone Bank, Polaris Bank, Jaiz Bank. Hypotheses were formulated and tested using Pearson Correlation Analysis instrument. The research findings confirmed that the level of interest rate on a bank loans, the cost of bank transactions, and unfair bank charges were positively affecting customer switching behavior in deposit money banks in Damaturu. Therefore, based on the findings drawn from this study, the following recommendations are propounded in order to achieve the main objective of the study; the banks management should review their levels of interest rates on loans, transactions cost and unfair bank charges if the banks are to retain their existing customers and attract new ones because high transaction fees and charges have a negative impact on customer switching behavior in banking sector. And finally CBN should also review the policy of banks charges imposing on banks as it was also contributing toward banks losing customers and customers losing confidence in banks.